In silico identification and characterization of the SNPs in the human ASTL gene and their probable role in female infertility - Suri, Kapali; Rajput, Neha; Sharma, Priya; Omble, Aishwarya D.; Kulkarni, Kiran; Gahlay, Gagandeep K. (Frontiers in Cell and Developmental Biology, 2023)
A key defense against polyspermy, the cortical reaction occurs minutes after the sperm and egg fuse and involves the exocytosis of cortical granules (CGs). The exocytosed CGs fuse with the plasma membrane of the egg and release their contents. Ovastacin (ASTL), a zinc metalloprotease, is released from CGs and cleaves ZP2, one of the four primary glycoproteins of human zona pellucida. This prevents polyspermy and protects the pre-implantation embryo. Any perturbation in the activity of ASTL and thus cleavage of ZP2, can disturb this process and may lead to infertility without changing the gross morphology of the oocyte. Female infertility has been associated with an increasing number of genetic variations called Single Nucleotide Polymorphisms (SNPs). In order to identify and understand the structural and functional effects of deleterious SNPs of ASTL on its interaction with ZP2 and hence on fertility, a total of 4748 SNPs from the dbSNP database were evaluated using a variety of in silico tools. 39 out of the 41 shortlisted nsSNPs were present in the catalytic domain and one each in the signal sequence and pro-domain of the protein. Comparison of the wild type with mutants using MutPred2 suggests an alteration in catalytic activity/zinc binding site in many SNPs. Docking studies show the involvement of hydrophobic interactions and H bonding between ASTL and ZP2. Two of the positions involved in hydrophobic interaction (P105 and D200) and 2 in H bonding (E75 and R159) have SNP’s associated with them validating their importance. Interestingly, a cluster of multiple SNPs was found in the motif 198DRD200, which is also a well-conserved region among several species. Thus, these results attempt to identify the regions in ASTL, mutations in which can cause idiopathic female infertility.